OPTIMIZATION OF PUMPING RELATED ENERGY USE AND COST IN A MUNICIPAL DRINKING WATER SYSTEM - Luthin, Adam (My University, 2019)
In terms of water production, Madison Water Utility (MWU) is the largest groundwater-sourced utility in the state of Wisconsin (Bohnert, 2012). In 2017 alone, MWU pumped 9.42 billion gallons of water while consuming 20.3 GWh of electrical energy at a cost of $2.16 million (PSC, 2017). Research states that water utilities can attribute over 80% of electrical energy consumption to pumping operations (Baniel, 2013; Elliott, 2003; Hamilton, 2009) thus equating to over 16.2 GWh at a cost of at least $1.7 million for MWU in 2017. Over the past 8 years, MWU has funded research aimed at reducing energy consumption and energy related costs from their pumping operation. This study is the latest of that research and focuses on building optimized pumping strategies for MWU’s distribution system. The objectives of this research were: 1. Develop procedures to optimize the operational strategies of all pumps within a pressure zone in terms of energy and cost. 2. Estimate annual energy and cost savings potential of optimized operational strategies in comparison to typical pump operation. 3. Estimate the potential energy and cost savings of investments in VFDs used in an optimized operational strategy.